Dreams and nightmares : immigration policy, youth, and families - Zatz, Marjorie Sue, 1955-; Rodriguez, Nancy (University of California Press, 2015)
"Dreams and Nightmares takes a critical look at the challenges and dilemmas of immigration policy and practice in the absence of comprehensive immigration reform. The experiences of children and youth provide a prism through which the interwoven dynamics and consequences of immigration policy become apparent. Using a unique sociolegal perspective, authors Zatz and Rodriguez examine the mechanisms by which immigration policies and practices mitigate or exacerbate harm to vulnerable youth. They pay particular attention to prosecutorial discretion, assessing its potential and limitations for resolving issues involving parental detention and deportation, unaccompanied minors, and Dreamers who came to the United States as young children. The book demonstrates how these policies and practices offer a means of prioritizing immigration enforcement in ways that alleviate harm to children, and why they remain controversial and vulnerable to political challenges"--Provided by publisher